Enhancement of a one-step membrane technique for the treatment of large bone defects by pre-seeding the membrane with CD8 lymphocyte depleted bone marrow mononuclear cells in a rat femoral defect model - Penna-Martinez, Marissa; Kammerer, Andreas; Stützle, Pia; Fees, Sabatian; Behr, Savina; Schaible, Inna; Schröder, Katrin; Verboket, René Danilo; Neijhoft, Jonas; Marzi, Ingo; Nau, Christoph; Henrich, Dirk (Frontiers in Immunology, 2024)
Background: The one-step membrane technique, using a human acellular dermal matrix (hADM), is an experimental method for treating large bone defects. This eliminates the need for the Masquelet membrane induction step, shortening the procedure while maintaining effectiveness. However, previous studies showed that colonizing hADM with bone marrow mononuclear cells (BMC) worsens healing, likely due to the presence of CD8+ lymphocytes, which negatively affect bone regeneration. This study aims to investigate whether the negative impact of BMC on bone healing in this technique is due to the CD8+ cell population. Materials and Methods: A 5 mm femoral defect was created in 25 male Sprague-Dawley rats, divided into three groups (G1-G3). BMC were isolated from syngenic donor rats, with CD8+ lymphocytes removed magnetically from the BMC fraction in one group. The defects were filled with bone chips and wrapped with differently treated hADM: G1 received native hADM, G2 received hADM+BMC, and G3 received hADM+BMC-CD8. After 8 weeks, the femurs were evaluated through radiological, biomechanical, and histological examinations. Results: Bone defects and bone mineral density (BMD) were significantly improved in G3 (hADM+BMC-CD8) compared to G2 (hADM+BMC). Bone volume, bone formation, and median bending stiffness were higher in G3. Immunohistological analysis showed a significant decrease in CD8 cell count in G3, with a lower percentage of IFNγ-producing cells compared to G2. Conclusion: Depleting CD8+ cells from BMC before colonizing hADM significantly improved bone healing, likely due to changes in the local mediator environment. This suggests that preoperative colonization with CD8+-depleted BMC could enhance the one-step membrane technique.